Coffee Roast Bean Product in Bandung - Amanda Nurviyan; Syahputra Syahputra (Akademi Sekretari Manajemen Taruna Bakti, 2019)
Lifestyle changes especially in big cities of Indonesia make the coffee business grow, upstream to downstream line. Many entrepreneurs not only have coffee shop but also coffee roastery which produces roast beans. One of these is Kopi Dewa. It is an emerging startup facing new competitors every day that make it require new strategy to maintain its existence and win a bigger market. Related to this phenomenon, this study aims to determine the external factors and internal factors of Kopi Dewa in order to survive and thrive. The purpose of this research is to formulate competitive strategy of Kopi Dewa’s roast bean. This research method uses descriptive quantitative method. Data are obtained through interview, observation, questionnaire, and literature studies. These are done through, first, identifying internal and external factors of Kopi Dewa. Furthermore, these factors are shortened and given weights, ratings, and scores on the IFAS matrix and EFAS matrix. The results of both matrix show that Kopi Dewa position is included into first quadrant in the Cartesian SWOT diagram, which means growth strategy is a good strategy for Kopi Dewa in the present. Both matrix components are mapped in the TOWS Matrix and given four alternative strategies. All four alternative strategies are ranked from the most important to be implemented to the least executed. These are Growth Strategy (market penetration), followed by service quality, pause strategy, and market penetration consecutively. Keywords: business strategy, competitive strategy, coffee roast bean product, SWOT analysis